LKB1 when associated with methylatedERα is a marker of bad prognosis in breast cancer. Issue 6 (4th March 2014) - Bouchekioua‐Bouzaghou, Katia; Poulard, Coralie; Rambaud, Juliette; Lavergne, Emilie; Hussein, Nader; Billaud, Marc; Bachelot, Thomas; Chabaud, Sylvie; Mader, Sylvie; Dayan, Guila; Treilleux, Isabelle; Corbo, Laura; et al.
<x xml:space="preserve">Abstract</x> Although the presence of nuclear estrogen receptor is widely used to guide breast cancer therapy, less attention has been paid to the receptor cytoplasmic signaling. Recently, we have shown that this pathway is operative in vivo and is activated in aggressive tumors representing a new potential target for breast cancer therapy. Here, we identified LKB1 as a partner of ERα and we explored its potential role in estrogen nongenomic signaling. The associations between LKB1 expression and the actors of this pathway, namely the methylated form of ERα (metERα), Src and PI3K, have been analyzed both in cultured cells and in 154 primary breast tumor samples. We found that LKB1 is a component of the cytoplasmic signaling complex in breast cell lines as well as in primary breast tumors. Moreover, an inverse correlation between the localization of LKB1 in nuclear and cytoplasmic compartments is observed. Importantly, high expression of cytoplasmic LKB1 is an independent marker of poor prognosis, associated with reduced overall survival (OS) and disease free survival (DFS). Conversely, the presence of nuclear LKB1 associates with increased OS and DFS. In conclusion, our results highlight that LKB1 expression in breast cancer appears to have opposite effects depending on its subcellular localization and may be used as a new prognostic biomarker.